2005
DOI: 10.1088/0741-3335/47/12b/s09
|View full text |Cite
|
Sign up to set email alerts
|

Safety factor profile requirements for electron ITB formation in TCV

Abstract: On the Tokamakà Configuration Variable (TCV), electron internal transport barriers (eITBs) can be formed during a gradual evolution from a centrally peaked to a hollow current profile while all external actuators are held constant. The formation occurs rapidly (<τ eE) and locally and, according to ASTRA modelling, is consistent with the appearance of a local minimum in the safety factor (q) profile. The eITB is sustained by non-inductively driven currents (including the off-axis bootstrap current) for many cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 24 publications
(23 reference statements)
1
42
0
Order By: Relevance
“…during the formation of the barrier or after the barrier was fully formed). With the aid of safety-factor profile modelling these results strongly suggested that rational q values do not play a role in the formation of the barrier, at least in the range 1.3 < q < 2.3 [6]. A conclusive proof would require a direct q-profile measurement.…”
Section: The Role Of the Current Density Profile In Eitbsmentioning
confidence: 98%
See 3 more Smart Citations
“…during the formation of the barrier or after the barrier was fully formed). With the aid of safety-factor profile modelling these results strongly suggested that rational q values do not play a role in the formation of the barrier, at least in the range 1.3 < q < 2.3 [6]. A conclusive proof would require a direct q-profile measurement.…”
Section: The Role Of the Current Density Profile In Eitbsmentioning
confidence: 98%
“…This high sensitivity to power deposition results in a certain degree of variability between nominally identical scenarios. However, the robustness of the configuration is greatly increased when a significant amount of power is deposited deliberately well inside the barrier in order to exploit the high confinement and optimize the overall plasma performance [6].…”
Section: The Properties and Dynamics Of Eitbsmentioning
confidence: 99%
See 2 more Smart Citations
“…The components of PTI include mitogen-activated protein kinase (MAPK) activation [3], defense-related gene expression, and callose deposition [2,4,5]. On the other hand, many pathogens secret multiple specific effectors to inhibit PTI in host plants [6][7][8], which, however, have developed the second line of defense comprising resistance (R) proteins that target corresponding pathogen effectors, resulting in effector-triggered immunity (ETI) [9] hypersensitive response (HR) at the infected site to inhibit the growth of biotrophic pathogens [1,2].…”
mentioning
confidence: 99%